Psychoanalytical Conflict, Anxiety, and Ego Defense Mechanism of Aza Holmes in John Green’s Turtles All the Way Down - Yunindya Palarani; Hadiyanto Hadiyanto (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2022)
This research aims to explain the psychoanalytical conflict, anxiety, and the ego defense mechanism of Aza Holmes by using Sigmund Freud’s psychoanalysis theory. The method of approach used in this research is the Psychology of Literature approach, while the method of collecting the data is library research. The primary data comes from the novel Turtles All the Way Down written by John Green and the secondary data comes from other text-based sources related to Freud’s Psychoanalysis theory. Furthermore, this research suggests that Aza Holmes’ ego is weak which causes her to conflict with her own self and other people around her. This conflict leads to the rising of her neurotic and moral anxieties. To relieve the tension of her anxiety, Aza Holmes performs some ego defense mechanisms such as projection, fixation, and displacement. Keywords: personality structure; psychoanalytical conflict; anxiety; ego defense mechanism; Freudian psychanalysis